Smart pressure management extension for EPANET: source code enhancement with a dynamic pressure reducing valve model. Issue 3 (25th March 2022) - Koşucu, Mehmet Melih; Demirel, Mehmet Cüneyd
Abstract: Applying pressure management reduces lost water and excessive hydraulic pressures in water distribution networks (WDNs). There are currently four different types of pressure management in the literature, i.e. fixed outlet, time modulated, flow modulated, and remote node modulated. The primary device used in pressure management is the pressure reducing valve (PRV) that dynamically controls the outlet pressure by moving up and down its main valve element. In this study, we firstly introduce the dynamic PRV model with four different pressure management types to the source code of EPANET v3.1 software and assess the effect of different valve opening schemes on pressure graphs and leakage quantities. The results showed that dynamic PRV significantly reduces lost water amounts and excessive hydraulic pressures in the WDN when valve opening is continuously adjusted. Our smart PM extension implemented into EPANET v3.1 software is publicly available in Zenodo repositories (https://zenodo.org/record/6243078 ). HIGHLIGHTS: The dynamic PRV model is introduced to EPANET 3. Four different PM schemes are incorporated into EPANET 3. The newly introduced EPANET 3 code is rigorously tested in the hydraulic model of two water distribution networks. Graphical Abstract